All-Optical Nanoscale Microring Device and System Design for Nano Communication - N. Sangwaranatee; N.W. Sangwaranatee; C. Teeka; P.P. Yupapin (My University, 2012)
In this paper, we have shown that the two components (TE and TM waves) of polarized light are manipulated by using the orthogonal soliton pair within a PANDA ring resonator known as a dark-bright soliton pair. In operation, the orthogonal soliton sets can be generated by using the system. The optical field is fed into the ring resonator system, which is controlled by an optical switch by using a single microring. To form the initial spin states, the magnetic field is induced by an aluminum plate (Al) coupled on AlGaAs waveguides for optoelectronic spin-up and - down states. The optoelectronic spin is formed by using the TE and TM wave components. In this manipulation, the electromagnetic radiation is formed by using the orthogonal soliton pulses. In fact, they are photons, which behave like elementary particles. Hence, the spin axis of photon is always parallel to its direction of motion. Many orthogonal sets are also available and existed, in which the spin conservation of many particles is maintained for large scale system use. Therefore, for future applications, the use for high performance storage, low power magnetic logic, quantum logic, quantum gate, nano antenna, nano radio, and applications of spintronic sensing can be realized based on realistic device parameters.
Keywords: Photonic and Optical Devices